Exploration of three-dimensional mesenchymal stem cells culture: a literature review - Meliawati, Widia; Wiratmini, Ngurah Intan; Rofaani, Elrade (Jurnal Biologi Udayana; Vol 29 No 1 (2025): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2025.v29.i01.p02, 2025)
Three-dimensional culture system provides a relevant physicochemical environment in vivo. It overcomes the limitations of traditional 2D cell culture in terms of mimicking cells morphology and physiology. In this literature review, various 3D culture methods, such as biomaterial-based scaffolds, synthetic polymer-based scaffolds, scaffold-free methods, and hydrogel scaffolds-based culture were analyzed to evaluate their advantages, disadvantages, and potentials. The results showed that various three-dimensional cultures exhibit different potentials, but are generally capable of supporting cell-to-cell and cell-matrix extracellular interactions, enhancing the viability, and biological functions of mesenchymal stem cells for utilization in many modern medicine. Three-dimensional culture also provides a stable environment for cell maintenance due to the even distribution of oxygen and nutrients that do not cause the properties of mesenchymal stem cells to be lost. It can be concluded that the three-dimensional culture method of mesenchymal stem cells is able to overcome the limitations of two-dimensional culture because it has a physiological environment similar to native tissues so it can establish interactions between cells and cells with extracellular matrix to increase the viability, proliferation, differentiation, and metabolic derivative of mesenchymal stem cells.